Communication competence during the preparation phase of the direct selling communication activities - Omar, Nuredayu (Elsevier Ltd., 2014)
In understanding the communication competence components in the direct marketing business, this study was performed.The objectives of the paper are to identify the communication activities that represent communication competence components and the outcome of communication competence components in the Preparation Phase of the direct selling activities.Interview and observation method were employed.Acquiring knowledge related to the business and spirituality; and preparing to acquire savoirs have been demonstrated in the Preparation Phase.These preparations demonstrated direct sellers’ cognitive, behavioural, and spiritual-affective abilities.The outcome that emerged from the findings were the preparation in developing their self-confidence, enthusiastic feelings, understanding of savoirs; and becoming knowledgeable of the business